Students’ attitudes about the ethics of using animals for experimental purposes - Milutinović, Jelena D (Scripta Medica, 2019)
This study aims at discovering the ethics level of the students who are attending the Faculty of Medical Sciences, the Faculty of Engineering Sciences and postgraduate students with experience of use laboratory animals in experimental purposes at University of Kragujevac. Focus of this study is on ethical segment of use of laboratory animals for experimental purposes and the correlation between the manifested level of ethics and various other factors like gender, high-school education, GPA, educational level of parents and desired affiliation after the graduation. The cross sectional study was conducted with 175 participants. In data collection, a questionnaire was used consisting of questions concerning sociodemographical characteristics and two scales – Gallup and Beckstead’s scale and a scale specially designed for the purposes of this research. The data were processed by using the methods of descriptive statistics, t-test for independent samples, single factor analysis of variance and Pearson’s correlation coefficient. The results have shown that the correlation between the manifested level of ethics of using animals in experimental purposes and gender, high-school education, grade point average, field of study or desired affiliation after the graduation is statistically significant. The differences in the results between students of pharmacy and the students of engineering sciences are also statistically significant. Cronbach’s alpha were estimated at 0.786, which implies that the internal consistency of scales shows significantly high level of reliability. The students from both fields, pharmacy and mechanical engineering, have shown a considerable level of ethics concerning the use of animals for laboratory purposes. Key words: ethics, laboratory animal, attitude